Evolution of Cryptographic Techniques: Overview of the Existing Approaches and Trends of the Development - Abid, Noman (CV. Multi Kreasi Media, 2022)
Cryptography remains to be one of the oldest and indispensable principles of today’s information protection disciplines because it gives indispensable tools for protecting content and messages during the communicational and data transferring actions. This review surveys extant research on possible cryptographic methods and their applications in different fields comprising of conventional key-based and new-complexity key based cryptography, cryptography based on Block chain, Homomorphic Cryptography, Post Quantum Cryptography and other types of cryptography. New complicated threats, emergence of Quantum computing, AI, block chain, and 5G, IoT are posing new threats and challenges and opportunities in cryptography. In this paper, some of these areas to key issues include: problems such as vulnerability of the traditional cryptographic system to brute force attacks, the impact of new developments in quantum computing to current encryption security systems, and the problem of key management, and side channel attacks. This article addresses how cryptography is used in protecting emerging technologies such as how light weight cryptography is incorporated to IoT peripherals, how works cryptography is applied to block chain or crypto currencies, and artificial intelligence systems. While with the arrival of quantum computing capable of threatening the security of classical cryptographic methods, the focus of the cryptographic community shifts to post quantum options like QKD and lattices. The next section of the review also talks about directions for future development direction of cryptography, and emphasizes the importance of creating new cryptographic algorithm that caters for the demand of scalability efficient and security to meet the increasing development in technologies. Cryptology is still needed for protection of relevant information and for proving secure communication for the age of integrated and computer-oriented society. The further evolution of intricate cryptographic methods and their integration into the advanced technologies is useful to combat new threats and guarantee safety of information that is to be necessary in the following years.